Strategies for communicating scientific evidence on healthcare to managers and the population: a scoping review - Rachel Riera; Carolina de Oliveira Cruz Latorraca; Roberta Carreira Moreira Padovez; Rafael Leite Pacheco; Davi Mamblona Marques Romão; Jorge Otávio Maia Barreto; Maria Lúcia Teixeira Machado; Romeu Gomes; Silvio Fernandes da Silva; Ana Luiza Cabrera Martimbianco (BMC, 2023)
Abstract Background Health evidence needs to be communicated and disseminated in a manner that is clearly understood by decision-makers. As an inherent component of health knowledge translation, communicating results of scientific studies, effects of interventions and health risk estimates, in addition to understanding key concepts of clinical epidemiology and interpreting evidence, represent a set of essential instruments to reduce the gap between science and practice. The advancement of digital and social media has reshaped the concept of health communication, introducing new, direct and powerful communication platforms and gateways between researchers and the public. The objective of this scoping review was to identify strategies for communicating scientific evidence in healthcare to managers and/or population. Methods We searched Cochrane Library, Embase®, MEDLINE® and other six electronic databases, in addition to grey literature, relevant websites from related organizations for studies, documents or reports published from 2000, addressing any strategy for communicating scientific evidence on healthcare to managers and/or population. Results Our search identified 24 598 unique records, of which 80 met the inclusion criteria and addressed 78 strategies. Most strategies focused on risk and benefit communication in health, were presented by textual format and had been implemented and somehow evaluated. Among the strategies evaluated and appearing to yield some benefit are (i) risk/benefit communication: natural frequencies instead of percentages, absolute risk instead relative risk and number needed to treat, numerical instead nominal communication, mortality instead survival; negative or loss content appear to be more effective than positive or gain content; (ii) evidence synthesis: plain languages summaries to communicate the results of Cochrane reviews to the community were perceived as more reliable, easier to find and understand, and better to support decisions than the original summaries; (iii) teaching/learning: the Informed Health Choices resources seem to be effective for improving critical thinking skills. Conclusion Our findings contribute to both the knowledge translation process by identifying communication strategies with potential for immediate implementation and to future research by recognizing the need to evaluate the clinical and social impact of other strategies to support evidence-informed policies. Trial registration protocol is prospectively available in MedArxiv (doi.org/10.1101/2021.11.04.21265922).